Endoscopic ultrasound‐guided tissue acquisition for focal liver lesions in patients with a history of multiple primary malignant neoplasms - Yuichi Takano; Naoki Tamai; Masataka Yamawaki; Jun Noda; Tetsushi Azami; Fumitaka Niiya; Fumiya Nishimoto; Naotaka Maruoka; Tatsuya Yamagami; Masatsugu Nagahama (DEN Open)
Abstract Objective This study aimed to investigate the usefulness of endoscopic ultrasound‐guided tissue acquisition (EUS‐TA) for diagnosing focal liver lesions in patients with a history of multiple primary malignant neoplasms. Methods Among patients who underwent EUS‐TA for focal liver lesions between 2016 and 2022, those with a history of multiple malignant neoplasms were included. A histologically confirmed malignant tumor within the past 5 years before EUS‐TA was defined as a history of malignant neoplasm. The primary outcomes were diagnostic ability and adverse events of EUS‐TA. Results This study included 16 patients (median age, 73 [33–90] years), the median tumor size was 32 (6–51) mm, 14 had a history of double malignant neoplasms, whereas two had triple malignant neoplasms. Malignant neoplasms were detected histologically or cytologically in all cases. Immunohistochemistry was performed in 75% (12/16), and the final diagnosis of EUS‐TA was metastatic liver tumor in 12 patients, and primary malignant liver tumor in four patients. The primary site could be identified in 11 of 12 metastatic tumor cases. The diagnostic yield of EUS‐TA was 100% (16/16) for differentiating benign and malignant tumors and 94% (15/16) for confirming the histological type including the primary site of metastatic lesions. No adverse events were associated with the procedure. Conclusion EUS‐TA is a useful diagnostic modality for focal liver lesions in patients with a history of multiple malignant neoplasms, allowing for the differential diagnosis of primary and metastatic tumors and identification of the primary site of metastatic lesions.